Manajemen Organisasi Persatuan Islam dalam Bidang Tarbiyah - Algifari, Muhammad Yusuf; Suparto, Suparto (Tadbir: Jurnal Manajemen Dakwah, 2024)
The appearance of Islamic Unity on the stage of Islamic history in Indonesia at the beginning of the 20th century has given a new pattern and color to the movement for the renewal islamic thought. It was precisely born as an answer to the complex challenges of the condition of the Muslim Ummah which was drowning in impatience or stagnation on rational thinking, mired in a life of great mysticism, the growth and development of khurafat, heresy adan superstition as well polytheism which was rampant at that time. Moreever, Muslims were very shackled by Dutch colonial rule which was very persistent in extinguishing the light of Islam. This situation inspired the emergence of the Islamic reformist movement which in turn initiated growing intellectual contacts that influenced the indonesian islamic community to reform islamic thought. Then the existence of this Islamic unity organization makes a contribution that plays an active role in education management which is very well organized by keeping up with current development without eliminating the original elements of islamic boarding school education.